Design And Characterisation of Generalised Similarity: Notion of Oblique Symmetry - Bruce, Bemena; Armand, Armand; Aurélien, Jerson; André, Totohasina; Daniel Rajaonasy, Feno (Journal of Research and Multidisciplinary, 2025)
In the literature, few topics deal with the generality of geometric characterization of this application. Obviously, this is not a strange application. For a direct view, it is very easy to give a conjecture that it looks like the sum of a direct similarity and of an indirect similarity. However, by making some in-depth studies concerning the properties diffuse geometrics in this application this is not quite the case. Subsequently, this paper will explain some rich geometric properties provided by this application.